Graphene quantum dots for ultrasensitive detection of acetylcholinesterase and its inhibitors - Li, Nan (2016)
Graphene quantum dots (GQDs) are emerging zero-dimensional materials promising a wide spectrum of novel applications including development of optical sensors. Herein, a GQD-based fluorometric sensor is devised to detect acetylcholinesterase (AChE, a critical enzyme in central nervous system and neuromuscular junctions) with an ultralow detection limit (0.58 pM with S/N of 5.0), using a photoluminescence 'turn-off' mechanism. This simple 'mix-and-detect' platform can also be employed to sense a variety of compounds that can directly or indirectly inhibit the enzymatic activities of AChE, such as nerve gases, pesticides, and therapeutic drugs. As the proof-of-concept demonstrations, we show the sensitive detection of paraoxon (a pesticide), tacrine (a drug to treat Alzheimer's disease), and dopamine (an important neurotransmitter).